(untitled) (Ameghiniana, 2013)
The Gualcamayo shales (Ordovician) that crops out in the northem Argentine Precordillera (La Rioja and San Juan Provinces) bear a rich graptolite fauna which is composed mainly by dichograptids and scandent bis erial rhabdosomes. Some specimens from Isograptus Moberg genus, collected in the lower pan of this formation, are described in this paper. The assemblage of Isograptus victoriae victoriae, lsograptus caduceus caduceus, Isograplus caduceus australis and Isograptus sp. indet. in the northem area of these outcrops (Peña Sombría, quebrada de Los Sapitos, quebrada Potrerillos and Quebrada del río Gualcamayo) allows to assign the shales basal levels to the Upper Arenigian. In the Sierra de Perico lsograptus victoriae cf. I. v. divergens and Paraglossograptus tentaculatus coexist and this suggests a Late Upper Arenigian to Lower Llanvirnian age for the graptolite bearing layers.